Flame-retardant wear-resistant foaming sole material and preparation process thereof

Through the specific process of preparing materials such as grafted polyethylene and compatibility agents, the problem of insufficient heat resistance of existing sole materials in high temperature environments is solved, and the efficient preparation of flame retardant and wear-resistant foamed sole materials is achieved, which improves the thermal stability and compatibility of the materials, and ensures safety and performance in high temperature environments.

CN120399455APending Publication Date: 2025-08-01VICTORY SPORTS GOODS CO LTD (DONGGUAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510693289.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing sole foaming materials are insufficient in high-temperature environments, resulting in reduced performance and cannot effectively protect the wearer from flames and high-temperature damage.

Method used

By preparing grafted polyethylene, compatibilizer and vinyl MQ, combined with nanotitanium dioxide and other materials, kneading and hot pressing is used to form flame-retardant and wear-resistant foamed sole materials, improving the thermal stability and compatibility of the materials.

Benefits of technology

It significantly improves the flame retardant and wear resistance of the material, ensures good grip and cushioning performance in high temperature environments, and improves the safety of staff.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399455A_ABST
    Figure CN120399455A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sole materials, in particular to a flame-retardant wear-resistant foaming sole material and a preparation process thereof. Comprising the following steps: preparing grafted polyethylene; preparing a compatilizer; vinyl MQ is prepared; and preparing the flame-retardant wear-resistant foaming sole material. According to the invention, 3, 5-dimethyl benzoate methyl ester is used on polyethylene, diisopropyl azodicarboxylate is used as an initiator, diisopropyl azodicarboxylate can initiate a grafting reaction at a low temperature, and compared with a traditional peroxide initiator, free radicals generated by decomposition of diisopropyl azodicarboxylate are more stable, so that the stability of the polyethylene is improved; degradation of a polyethylene main chain can be effectively reduced, grafting efficiency is improved, certain physical crosslinking points are formed among grafted polyethylene molecular chains through polar groups such as ester groups, and the crosslinking points can limit movement of the molecular chains to a certain extent, so that heat resistance and flame retardance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sole materials, and particularly relates to a flame-retardant and wear-resistant foamed sole material and a preparation process thereof. Background Art

[0002] A foamed material is a lightweight, porous material formed by introducing a large number of air holes into a polymer matrix through physical or chemical methods. Its internal structure usually contains a large number of tiny bubbles, which can be closed-cell or open-cell structures, endowing the material with unique physical and mechanical properties. The foamed material has a low density, can significantly reduce the weight of the sole, and at the same time can absorb and release energy, providing good cushioning and resilience, reducing the impact on the feet and joints during walking or exercise, and is widely used in sole materials due to its unique properties.

[0003] In some high-risk environments, such as chemical plants, oil drilling platforms, electrical equipment operation sites, etc., flame-retardant soles are essential. These places have flammable and explosive substances or high-temperature environments. The flame-retardant material can effectively protect the wearer's feet from the harm of flames and high temperatures. At the same time, the wear-resistant material can maintain the shape and structure of the sole, ensuring that the shoes maintain good grip and cushioning performance, thereby improving the safety of workers in high-risk environments.

[0004] Common sole foamed materials include ethylene-vinyl acetate copolymer, thermoplastic polyurethane elastomer, and thermoplastic polyester elastomer. These materials are lightweight, wear-resistant, flexible, and comfortable to wear, and are commonly used as sole materials for sports shoes. However, their heat resistance is limited, and their performance is prone to decline in high-temperature environments. Therefore, the present invention provides a flame-retardant and wear-resistant foamed sole material and a preparation process thereof to solve the problems existing in the above-mentioned prior art. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a flame-retardant and wear-resistant foamed sole material and a preparation process thereof.

[0006] A preparation process of a flame-retardant and wear-resistant foamed sole material includes the following steps:

[0007] S1: Prepare grafted polyethylene

[0008] Add polyethylene and triphenylphosphine into tetrahydrofuran, then add 3,5-dimethyl benzoate, stir, and then add diisopropyl azodicarboxylate and 3,5-di-tert-butyl-4-hydroxytoluene, and continue to stir and react to obtain grafted polyethylene;

[0009] S2: Prepare a compatibilizer

[0010] Put the grafted polyethylene into a reaction flask, add xylene, and heat it. Then add concentrated sulfuric acid and hydroxypropyl silicone oil. After the reaction, dry it to obtain a compatibilizer;

[0011] S3: Prepare vinyl MQ

[0012] Mix tetramethyldivinyldisiloxane, deionized water, absolute ethanol and concentrated hydrochloric acid, stir and heat up simultaneously. Then add tetraethyl orthosilicate. After the reaction, extract the product with toluene, wash it with water, and dry it to obtain vinyl MQ;

[0013] S4: Prepare a flame-retardant, wear-resistant and foamed sole material

[0014] Add vinyl MQ and nano-titanium dioxide into a mixer for mixing, extract with acetone by reflux, then dry. Then add silicone oil, low-density polyethylene, initiator and compatibilizer. After mixing, add nano-silica, zinc oxide and calcium carbonate. After mixing, discharge the material, hot press and mold, vulcanize and cure to obtain a flame-retardant, wear-resistant and foamed sole material.

[0015] Further, the preparation of grafted polyethylene in step S1 includes the following steps:

[0016] Add 1-2 parts by volume of polyethylene and 3-5 parts by volume of triphenylphosphine into 20-25 parts by volume of tetrahydrofuran. Then add 3-4 parts by volume of 3,5-dimethylbenzoate, stir for 15-20 min, add 0.3-0.5 parts by volume of diisopropyl azodicarboxylate and 0.2-0.5 parts by volume of 3,5-di-tert-butyl-4-hydroxytoluene, and continue to stir for 16-18 h for reaction. After the reaction, precipitate the product, filter it, perform ultrasonic treatment 3 times, and dry it in a vacuum drying oven for 24-26 h to obtain grafted polyethylene.

[0017] Further, the preparation of the compatibilizer in step S2 includes the following steps:

[0018] Add 12-15 parts by mass of grafted polyethylene into a reaction flask, add 240-250 parts by mass of xylene, and heat to 120-125 °C. Then add 0.1-0.5 parts by mass of concentrated sulfuric acid and 58-60 parts by mass of hydroxypropyl silicone oil. After reacting for 8-9 h, filter, wash the precipitate until neutral, and then dry it at 60-65 °C for 5-6 h to obtain a compatibilizer.

[0019] Further, the preparation of vinyl MQ in step S3 includes the following steps:

[0020] 22-25 parts by mass of tetramethyldivinyldisiloxane, 16-20 parts by mass of deionized water, 10-12 parts by mass of anhydrous ethanol and 2.2-2.5 parts by mass of concentrated hydrochloric acid are mixed and stirred, and the temperature is raised to 70-75° C. while stirring. Subsequently, 40-45 parts by mass of ethyl orthosilicate are added. After reacting for 3-3.5 hours, the product is extracted with toluene, washed with water three times, dried, and the solvent is removed by rotary evaporation to obtain vinyl MQ.

[0021] Furthermore, step S3 of preparing a flame-retardant and wear-resistant foamed sole material comprises the following steps:

[0022] 100-105 parts by weight of vinyl MQ and 30-35 parts by weight of nano titanium dioxide were added to a mixer, mixed at 120-130°C and 100-120 r / min for 10-15 minutes, refluxed with acetone at 85-90°C for 24-26 hours, then dried at 70-75°C for 12-14 hours, and then 2-3 parts by weight of silicone oil, 20-25 parts by weight of low-density polyethylene, 0.6-1 parts by weight of methyl methacrylate were added to the mixer. The invention discloses a flame retardant and wear-resistant foamed sole material, wherein the flame retardant and wear-resistant foamed sole material is prepared by mixing 0.5-2 parts by mass of an initiator and 0.5-2 parts by mass of a compatibilizer, mixing for 10-12 minutes, then adding 8-10 parts by mass of nano-silicon dioxide, 2-3 parts by mass of zinc oxide and 2-4 parts by mass of calcium carbonate, mixing for 10-15 minutes, discharging the material, standing for 24 hours, hot pressing at 180-190°C and 20MPa, vulcanizing for 20-25 minutes, and hot air drying and curing at 180-190°C for 2-2.5 hours.

[0023] Furthermore, the concentration of concentrated sulfuric acid is 80-98%.

[0024] Furthermore, the concentration of concentrated hydrochloric acid is 35-38%.

[0025] Furthermore, the initiator is benzoyl peroxide.

[0026] Furthermore, the density of low-density polyethylene is 0.91-0.94 g / cm 3 .

[0027] A flame retardant and wear-resistant foamed sole material is prepared by a preparation process of the flame retardant and wear-resistant foamed sole material.

[0028] Compared with the prior art, the present invention has at least the following beneficial effects:

[0029] 1. In the present invention, methyl 3,5-dimethylbenzoate is used on polyethylene, and diisopropyl azodicarboxylate is used as an initiator. Diisopropyl azodicarboxylate can initiate grafting reactions at relatively low temperatures. Compared with traditional peroxide initiators, the free radicals generated by the decomposition of diisopropyl azodicarboxylate are more stable, which can effectively reduce the degradation of the polyethylene main chain and improve the grafting efficiency. After grafting, the functional group benzene ring of methyl 3,5-dimethylbenzoate is introduced onto the surface of polyethylene. The presence of the benzene ring can improve the thermal stability of the polyethylene chain. After grafting, physical crosslinking points are also formed between the polyethylene molecular chains through polar groups such as ester groups. These crosslinking points can restrict the movement of molecular chains to a certain extent, thereby improving the heat resistance and flame retardancy of the material.

[0030] 2. In the present invention, the grafted polyethylene is modified with hydroxypropyl silicone oil. After the grafting of hydroxypropyl silicone oil, polar groups hydroxyl and siloxy are introduced onto the surface of polyethylene, significantly improving the surface polarity and hydrophilicity. This improves the adhesion and compatibility between polyethylene and other materials, thereby enhancing the compatibility between raw materials. The prepared foamed sole material has good physical properties, is not easily decomposed, and is not easily worn. The surface hardness and wear resistance of polyethylene after grafting with hydroxypropyl silicone oil are significantly improved. This is because a protective layer is formed on the surface by the siloxy structure. The siloxy protective layer can physically isolate the surface of polyethylene from the external environment such as air and moisture, reducing direct contact and wear, thereby improving the wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings incorporated herein and constituting a part of the specification illustrate embodiments of the present disclosure and, together with the specification, are further used to explain the principles of the present disclosure and enable those skilled in the relevant art to implement and use the present disclosure.

[0032] Figure 1 It is a process flow chart of the preparation of a flame-retardant and wear-resistant foamed sole material adopted in the embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0033] The following describes in detail a flame-retardant and wear-resistant foamed sole material and its preparation process provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it should be noted here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments. For some well-known technologies, those skilled in the art can also adopt other alternative methods for implementation; and the accompanying drawings are only for more specific description of the embodiments and are not intended to specifically limit the present invention.

[0034] Example 1:

[0035] A preparation process of a flame-retardant and wear-resistant foamed sole material, as Figure 1 shown, includes the following steps:

[0036] S1: Preparation of grafted polyethylene

[0037] Add 1 volume part of polyethylene and 3 volume parts of triphenylphosphine to 20 volume parts of tetrahydrofuran. Subsequently, add 3 volume parts of 3,5-dimethyl benzoate, stir for 15 min, add 0.3 volume part of diisopropyl azodicarboxylate and 0.2 volume part of 3,5-di-tert-butyl-4-hydroxytoluene, and continue stirring for 16 h for reaction. After the reaction ends, precipitate the product, filter, perform ultrasonic treatment 3 times, and dry in a vacuum drying oven for 24 h to obtain grafted polyethylene.

[0038] S2: Preparation of compatibilizer

[0039] Add 12 mass parts of grafted polyethylene to a reaction flask, then add 240 mass parts of xylene, and heat to 120 °C. Subsequently, add 0.1 mass part of concentrated sulfuric acid and 58 mass parts of hydroxypropyl silicone oil. The concentration of the concentrated sulfuric acid is 80%. After reacting for 8 h, filter, wash the precipitate until neutral, and then dry at 60 °C for 5 h to obtain the compatibilizer.

[0040] S3: Preparation of vinyl MQ

[0041] Mix and stir 22 mass parts of tetramethyldivinyldisiloxane, 16 mass parts of deionized water, 10 mass parts of absolute ethanol, and 2.2 mass parts of concentrated hydrochloric acid. The concentration of the concentrated hydrochloric acid is 35%. While stirring, heat up to 70 °C. Subsequently, add 40 mass parts of tetraethyl orthosilicate. After reacting for 3 h, extract the product with toluene and wash it three times with water, dry it, and remove the solvent by rotary evaporation to obtain vinyl MQ.

[0042] S4: Preparation of flame-retardant and wear-resistant foamed sole material

[0043] Add 100 mass parts of vinyl MQ and 30 mass parts of nano-titanium dioxide to a mixer, mix at 120 °C and a rotation speed of 100 r / min for 10 min, reflux and extract with acetone at 85 °C for 24 h, then dry at 70 °C for 12 h. Then add 2 mass parts of silicone oil, 20 mass parts of low-density polyethylene, 0.6 mass part of initiator benzoyl peroxide, and 0.5 mass part of compatibilizer. The density of the low-density polyethylene is 0.91 g / cm 3 , mix for 10 min, then add 8 mass parts of nano-silica, 2 mass parts of zinc oxide, and 2 mass parts of calcium carbonate, discharge after mixing for 10 min, let stand for 24 h, hot press at 180 °C and 20 MPa, then vulcanize for 20 min, and cure by hot air drying at 180 °C for 2 h to obtain the flame-retardant and wear-resistant foamed sole material.

[0044] Example 2:

[0045] A preparation process of a flame-retardant and wear-resistant foamed sole material, as Figure 1 shown, includes the following steps:

[0046] S1: Preparation of grafted polyethylene

[0047] Add 2 parts by volume of polyethylene and 5 parts by volume of triphenylphosphine to 25 parts by volume of tetrahydrofuran. Subsequently, add 4 parts by volume of 3,5-dimethyl benzoate, stir for 15 min, add 0.5 part by volume of diisopropyl azodicarboxylate and 0.5 part by volume of 3,5-di-tert-butyl-4-hydroxytoluene, and continue stirring for 16 h for reaction. After the reaction, precipitate the product, filter, perform ultrasonic treatment 3 times, and dry in a vacuum drying oven for 24 h to obtain grafted polyethylene.

[0048] S2: Preparation of compatibilizer

[0049] Add 15 parts by mass of grafted polyethylene to a reaction flask, then add 250 parts by mass of xylene, and heat to 120 °C. Subsequently, add 0.5 part by mass of concentrated sulfuric acid and 60 parts by mass of hydroxypropyl silicone oil. The concentration of the concentrated sulfuric acid is 90%. After reacting for 8 h, filter, wash the precipitate until neutral, and then dry at 60 °C for 5 h to obtain the compatibilizer.

[0050] S3: Preparation of vinyl MQ

[0051] Mix and stir 25 parts by mass of tetramethyldivinyldisiloxane, 20 parts by mass of deionized water, 12 parts by mass of absolute ethanol, and 2.5 parts by mass of concentrated hydrochloric acid. The concentration of the concentrated hydrochloric acid is 38%. While stirring, heat up to 70 °C, then add 45 parts by mass of tetraethyl orthosilicate. After reacting for 3 h, extract the product with toluene and wash with water three times, dry, and remove the solvent by rotary evaporation to obtain vinyl MQ.

[0052] S4: Preparation of flame-retardant and wear-resistant foamed sole material

[0053] Add 105 parts by mass of vinyl MQ and 35 parts by mass of nano-titanium dioxide to a mixer, mix at 120 °C and a rotation speed of 100 r / min for 10 min, perform reflux extraction with acetone at 85 °C for 24 h, then dry at 70 °C for 12 h. Then add 3 parts by mass of silicone oil, 25 parts by mass of low-density polyethylene, 1 part by mass of initiator benzoyl peroxide, and 2 parts by mass of compatibilizer. The density of the low-density polyethylene is 0.91 g / cm 3 , mix for 10 min, then add 10 parts by mass of nano-silica, 3 parts by mass of zinc oxide, and 4 parts by mass of calcium carbonate, discharge after mixing for 10 min, let stand for 24 h, hot press at 180 °C and 20 MPa, then vulcanize for 20 min, and cure by hot air drying at 180 °C for 2 h to obtain the flame-retardant and wear-resistant foamed sole material.

[0054] Example 3:

[0055] A preparation process of a flame-retardant and wear-resistant foamed sole material, as Figure 1As shown in the figure, it includes the following steps:

[0056] S1: Prepare grafted polyethylene

[0057] Add 1 part by volume of polyethylene and 3 parts by volume of triphenylphosphine to 20 parts by volume of tetrahydrofuran, then add 3 parts by volume of 3,5-dimethyl benzoate, stir for 20 min, add 0.3 part by volume of diisopropyl azodicarboxylate and 0.2 part by volume of 3,5-di-tert-butyl-4-hydroxytoluene, and continue to stir for 18 h for reaction. After the reaction ends, the product precipitates out, filter, perform ultrasonic treatment 3 times, and dry in a vacuum drying oven for 26 h to obtain grafted polyethylene.

[0058] S2: Prepare a compatibilizer

[0059] Add 12 parts by mass of grafted polyethylene to a reaction flask, then add 240 parts by mass of xylene, and heat to 125 °C. Then add 0.1 part by mass of concentrated sulfuric acid and 58 parts by mass of hydroxypropyl silicone oil. The concentration of the concentrated sulfuric acid is 95%. After reacting for 9 h, filter, wash the precipitate until neutral, and then dry at 65 °C for 6 h to obtain the compatibilizer.

[0060] S3: Prepare vinyl MQ

[0061] Mix and stir 22 parts by mass of tetramethyldivinyldisiloxane, 16 parts by mass of deionized water, 10 parts by mass of absolute ethanol and 2.2 parts by mass of concentrated hydrochloric acid. The concentration of the concentrated hydrochloric acid is 38%. While stirring, heat up to 75 °C, then add 40 parts by mass of tetraethyl orthosilicate. After reacting for 3.5 h, extract the product with toluene, wash with water three times, dry, and rotary evaporate to remove the solvent to obtain vinyl MQ.

[0062] S4: Prepare a flame-retardant, wear-resistant and foamed sole material

[0063] Add 100 parts by mass of vinyl MQ and 30 parts by mass of nano-titanium dioxide to a mixer, mix at 130 °C and a rotation speed of 120 r / min for 15 min, reflux and extract with acetone at 90 °C for 26 h, then dry at 75 °C for 14 h. Then add 2 parts by mass of silicone oil, 20 parts by mass of low-density polyethylene, 0.6 part by mass of initiator benzoyl peroxide and 0.5 part by mass of compatibilizer. The density of the low-density polyethylene is 3 0.91 g / cm, mix for 15 min, then add 8 parts by mass of nano-silica, 2 parts by mass of zinc oxide and 2 parts by mass of calcium carbonate, discharge after mixing for 15 min, let stand for 24 h, hot press at 190 °C and 20 MPa to form, then vulcanize for 25 min, and cure by hot air drying at 190 °C for 2.5 h to obtain the flame-retardant, wear-resistant and foamed sole material.

[0064] Example 4:

[0065] A preparation process of a flame retardant and wear-resistant foam sole material, such as Figure 1 As shown, the following steps are included:

[0066] S1: Preparation of grafted polyethylene

[0067] 1 part by volume of polyethylene and 3 parts by volume of triphenylphosphine were added to 20 parts by volume of tetrahydrofuran, followed by the addition of 3 parts by volume of 3,5-dimethylbenzoate, stirred for 15 minutes, 0.3 parts by volume of diisopropyl azodicarboxylate and 0.2 parts by volume of 3,5-di-tert-butyl-4-hydroxytoluene were added, and the stirring was continued for 16 hours. After the reaction was completed, the product was precipitated, filtered, ultrasonically treated 3 times, and dried in a vacuum drying oven for 24 hours to obtain grafted polyethylene.

[0068] S2: Preparation of compatibilizer

[0069] Add 12 parts by mass of grafted polyethylene to a reaction bottle, then add 240 parts by mass of xylene and heat to 120°C, then add 0.1 parts by mass of concentrated sulfuric acid and 58 parts by mass of hydroxypropyl silicone oil, the concentration of concentrated sulfuric acid is 80%, react for 8 hours, filter, wash the precipitate to neutrality, and then dry at 60°C for 5 hours to obtain a compatibilizer.

[0070] S3: Preparation of Vinyl MQ

[0071] 22 parts by mass of tetramethyldivinyldisiloxane, 16 parts by mass of deionized water, 10 parts by mass of anhydrous ethanol, and 2.2 parts by mass of concentrated hydrochloric acid were mixed and stirred. The concentration of the concentrated hydrochloric acid was 35%, and the temperature was raised to 70°C while stirring. Subsequently, 40 parts by mass of ethyl orthosilicate was added. After reacting for 3 hours, the product was extracted with toluene, washed with water three times, dried, and the solvent was removed by rotary evaporation to obtain vinyl MQ.

[0072] S4: Preparation of flame-retardant and wear-resistant foam sole materials

[0073] 100 parts by mass of vinyl MQ and 30 parts by mass of nano-titanium dioxide were added to a mixer, mixed at 120°C and 100 r / min for 10 minutes, reflux extracted with acetone at 85°C for 24 hours, and then dried at 70°C for 12 hours. Then, 2 parts by mass of silicone oil, 20 parts by mass of low-density polyethylene, 0.6 parts by mass of initiator benzoyl peroxide and 0.5 parts by mass of compatibilizer were added. The density of low-density polyethylene was 0.94 g / cm 3 After mixing for 12 minutes, 8 parts by mass of nano-silicon dioxide, 2 parts by mass of zinc oxide and 2 parts by mass of calcium carbonate were added, and the material was discharged after mixing for 12 minutes. It was allowed to stand for 24 hours, hot-pressed at 185°C and 20MPa, and then vulcanized for 22 minutes. It was dried and cured with hot air at 185°C for 2.2 hours to obtain a flame-retardant and wear-resistant foamed sole material.

[0074] Comparative Example 1:

[0075] Compared with Example 1, the difference in Comparative Example 1 is that 3,5-dimethyl benzoate is not added in step S1. Specifically, "S1: Prepare grafted polyethylene

[0076] Add 1 part by volume of polyethylene and 3 parts by volume of triphenylphosphine to 20 parts by volume of tetrahydrofuran, then stir for 15 min, add 0.3 part by volume of diisopropyl azodicarboxylate and 0.2 part by volume of 3,5-di-tert-butyl-4-hydroxytoluene, and continue stirring for 16 h for reaction. After the reaction, precipitate the product, filter, perform ultrasonic treatment 3 times, and dry in a vacuum drying oven for 24 h to obtain grafted polyethylene", and the remaining steps remain unchanged. The prepared flame-retardant and wear-resistant foamed sole material is denoted as Comparative Example 1.

[0077] Comparative Example 2:

[0078] Compared with Example 1, the difference in Comparative Example 2 is that hydroxypropyl silicone oil is not added in step S2. Specifically, "S2: Prepare compatibilizer

[0079] Add 12 parts by mass of grafted polyethylene to a reaction flask, then add 240 parts by mass of xylene, and heat to 120 °C. Subsequently, add 0.1 part by mass of concentrated sulfuric acid with a concentration of 80%. After reacting for 8 h, filter, wash the precipitate until neutral, and then dry at 60 °C for 5 h to obtain the compatibilizer", and the remaining steps remain unchanged. The prepared flame-retardant and wear-resistant foamed sole material is denoted as Comparative Example 2.

[0080] Comparative Example 3:

[0081] Comparative Example 3 is a commercially available foamed sole material.

[0082] Refer to the standard of GB / T8332-2008 "Test Method for Combustion Performance of Foamed Plastics" to test the flame-retardant performance of Examples 1-4 and Comparative Examples 1-3, as shown in Table 1;

[0083] Refer to the standard of GB / T 9867-2008 "Determination of Abrasion Resistance of Vulcanized Rubber or Thermoplastic Rubber (Rotating Cylinder Abrasion Machine Method)" to test the abrasion resistance of Examples 1-4 and Comparative Examples 1-3, as shown in Table 2.

[0084] Table 1

[0085] Oxygen Index / OI Example 1 42.1 Example 2 42.3 Example 3 42.1 Example 4 42.2 Comparative Example 1 37.4 Comparative Example 2 36.5 Comparative Example 3 38.2

[0086] Table 2

[0087] <![CDATA[Relative volume wear amount / mm 3 > Example 1 289.5 Example 2 290.6 Example 3 289.9 Example 4 290.4 Comparative Example 1 334.1 Comparative Example 2 337.6 Comparative Example 3 321.7

[0088] As can be seen from Table 1, the oxygen indices of Examples 1-4 are above 42.1, all higher than those of the comparative examples, indicating that the examples have better flame retardant properties. The specific raw material combination of the present invention can achieve a synergistic effect, thereby improving the high temperature resistance of the foamed sole material, and thus improving the flame retardant performance. Moreover, the oxygen indices of Examples 1-4 are higher than those of Comparative Example 3 of the commercially available product, indicating that the flame retardant performance of the present invention is better than that of the commercially available product.

[0089] As can be seen from Table 2, the relative volume wear of Examples 1-4 is below 290.6 mm 3 , while the wear of Comparative Example 1 and Comparative Example 2 reaches 334.1 mm 3 and 337.6 mm 3 , and the relative volume wear of Comparative Example 3 of the commercially available product is 321.7 mm 3 . It can be seen that the wear resistance of the present invention is higher than that of the commercially available product.

[0090] The above examples are only illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Any person familiar with this technology can modify or change the above examples without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A preparation process of a flame-retardant and wear-resistant foamed sole material, characterized in that, It includes the following steps: S1: Prepare grafted polyethylene Add polyethylene and triphenylphosphine into tetrahydrofuran, then add 3,5-dimethyl benzoate, stir, and then add diisopropyl azodicarboxylate and 3,5-di-tert-butyl-4-hydroxytoluene, and continue stirring and reacting to obtain grafted polyethylene; S2: Prepare compatibilizer Add grafted polyethylene into a reaction flask, then add xylene and heat, then add concentrated sulfuric acid and hydroxypropyl silicone oil, dry after reaction to obtain a compatibilizer; S3: Prepare vinyl MQ Mix and stir tetramethyldivinyldisiloxane, deionized water, absolute ethanol and concentrated hydrochloric acid while heating, then add tetraethyl orthosilicate, extract the product with toluene after reaction, wash with water, and dry to obtain vinyl MQ; S4: Prepare flame-retardant, wear-resistant and foamed sole material Add vinyl MQ and nano-titanium dioxide into a mixer for mixing, extract with acetone by reflux, then dry, then add silicone oil, low-density polyethylene, initiator and compatibilizer, mix, then add nano-silica, zinc oxide and calcium carbonate, mix and discharge, hot press and mold, vulcanize and cure to obtain a flame-retardant, wear-resistant and foamed sole material.

2. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 1, characterized in that, Step S1 for preparing grafted polyethylene includes the following steps: Add 1-2 parts by volume of polyethylene and 3-5 parts by volume of triphenylphosphine into 20-25 parts by volume of tetrahydrofuran, then add 3-4 parts by volume of 3,5-dimethyl benzoate, stir for 15-20 min, add 0.3-0.5 parts by volume of diisopropyl azodicarboxylate and 0.2-0.5 parts by volume of 3,5-di-tert-butyl-4-hydroxytoluene, and continue stirring and reacting for 16-18 h. After the reaction, precipitate the product, filter, perform ultrasonic treatment 3 times, and dry in a vacuum drying oven for 24-26 h to obtain grafted polyethylene.

3. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 2, characterized in that, Step S2 for preparing compatibilizer includes the following steps: Add 12-15 parts by mass of grafted polyethylene into a reaction flask, then add 240-250 parts by mass of xylene and heat to 120-125 °C, then add 0.1-0.5 parts by mass of concentrated sulfuric acid and 58-60 parts by mass of hydroxypropyl silicone oil, filter after reacting for 8-9 h, wash the precipitate until neutral, and then dry at 60-65 °C for 5-6 h to obtain a compatibilizer.

4. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 3, characterized in that, Step S3 for preparing vinyl MQ includes the following steps: Mix and stir 22-25 parts by mass of tetramethyldivinyldisiloxane, 16-20 parts by mass of deionized water, 10-12 parts by mass of absolute ethanol and 2.2-2.5 parts by mass of concentrated hydrochloric acid, stir and heat up to 70-75 °C at the same time, then add 40-45 parts by mass of tetraethyl orthosilicate, extract the product with toluene after reacting for 3-3.5 h, wash with water three times, dry, and remove the solvent by rotary evaporation to obtain vinyl MQ.

5. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 4, characterized in that, Step S3 for preparing flame-retardant, wear-resistant and foamed sole material includes the following steps: 100 - 105 parts by mass of vinyl MQ and 30 - 35 parts by mass of nano - titanium dioxide are added to a mixer, and kneaded at 120 - 130 °C and a rotation speed of 100 - 120 r / min for 10 - 15 min. Then, reflux extraction is carried out with acetone at 85 - 90 °C for 24 - 26 h, followed by drying at 70 - 75 °C for 12 - 14 h. Next, 2 - 3 parts by mass of silicone oil, 20 - 25 parts by mass of low - density polyethylene, 0.6 - 1 part by mass of initiator and 0.5 - 2 parts by mass of compatibilizer are added. After kneading for 10 - 12 min, 8 - 10 parts by mass of nano - silica, 2 - 3 parts by mass of zinc oxide and 2 - 4 parts by mass of calcium carbonate are added. After kneading for 10 - 15 min, the material is discharged, allowed to stand for 24 h, hot - pressed at 180 - 190 °C and 20 MPa to form a shape, then vulcanized for 20 - 25 min, and dried and cured by hot air at 180 - 190 °C for 2 - 2.5 h to obtain a flame - retardant and wear - resistant foamed sole material.

6. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 3, characterized in that, The concentration of concentrated sulfuric acid is 80 - 98%.

7. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 4, characterized in that, The concentration of concentrated hydrochloric acid is 35 - 38%.

8. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 5, characterized in that, The initiator is benzoyl peroxide.

9. The preparation process of a flame-retardant and wear-resistant foamed sole material according to claim 5, characterized in that, The density of low-density polyethylene is 0.91 - 0.94 g / cm 3 .

10. A flame-retardant and wear-resistant foamed sole material, characterized in that, It is prepared by the preparation process of the flame - retardant and wear - resistant foamed sole material according to any one of claims 1 - 9 above.